Assessment of mite fauna in different coffee cropping systems in Brazil - Peixoto, Marília Lara; Fernandes, Leda Gonçalves; Carvalho, Matheus Araújo Cardoso; Oliveira, Milena Leite de [UNESP]; Putti, Fernando Ferrari [UNESP]; Reis, André Rodrigues dos [UNESP] (Taylor & Francis, 2017)
Agro-ecological diversification may increase natural biodiversity and decrease environmental impacts caused by the intensification of management practices, especially with respect to pest control. This study aimed to evaluate mite populations from surveys in commercial coffee (Coffea arabica) orchards managed in different ways. Four different cropping systems were compared: a conventional system (CS), non-pesticide system (NPS), organic system (OS) and organic agroforestry system (OAS). Mite samples were taken from 24 coffee plantations (n = 6 for each management strategy). Six leaves per plant were collected from five sampling sites totalling 30 leaves from each plantation. Mites were removed from individual leaves, counted and identified to family level. Amongst the predatory mites, two families were detected; the Phytoseiidae was the most abundant family while the Stigmaeidae, generalist predatory mites, were only found in two management systems (NPS and AOS). Of the two families of phytophagous mites, the family Tenuipalpidae was the most abundant, but rarely found in AOS. The other phytophagous family, Tetranychidae, was less abundant in coffee crops than Tenuipalpidae, but the most abundant phytophagous family in CS. Understanding the relationship between mite populations and management practices can aid in choice of spraying strategies for different coffee management systems.
Keywords: biodiversity; Phytophagous; predatory mites; sustainability